2021
DOI: 10.21037/tcr-21-227
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reverses the sunitinib resistance in clear cell renal cell carcinoma (ccRCC) through the induction of ferroptosis via the ADAMTS18 gene

Abstract: Background:To explore the possible mechanism by which curcumin reverses the sunitinib resistance in clear cell renal cell carcinoma (ccRCC).Methods: A sunitinib-resistant ccRCC cell model was established. The MTT assay was used to determine the half maximal inhibitory concentration (IC 50 ) and drug resistance (DR) index. The effects of curcumin plus sunitinib or sunitinib alone on drug-resistant cell lines were verified by the cell counting kit-8 (CCK-8) assay, colony formation assay, and apoptosis assay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…For example, in NSCLC, curcumin could induce ferroptosis via autophagic activation to improve the therapeutic efficacy [ 18 ]. In ccRCC, curcumin promoted ferroptosis to reverse sunitinib resistance [ 19 ]. In breast cancer, curcumin suppressed tumorigenesis via enhancing SLC1A5-mediated ferroptosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in NSCLC, curcumin could induce ferroptosis via autophagic activation to improve the therapeutic efficacy [ 18 ]. In ccRCC, curcumin promoted ferroptosis to reverse sunitinib resistance [ 19 ]. In breast cancer, curcumin suppressed tumorigenesis via enhancing SLC1A5-mediated ferroptosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, identified and named a decade ago, is a unique type of programmed cell death primarily driven by iron-dependent lipid peroxidation [ 16 , 17 ]. Growing evidence has revealed that ferroptosis plays a crucial part in treatment with curcumin against various cancers, such as non-small-cell lung cancer (NSCLC) [ 18 ], clear cell renal cell carcinoma (ccRCC) [ 19 ], and breast cancer [ 20 , 21 ]. Despite these findings, however, the precise action of curcumin-modulated ferroptosis in HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin reversed resistance and enhanced the sensitivity of 786-O-DR (drug-resistant) cells to sunitinib. It reduced the iron content, upregulated the expression of the ADAMTS18 gene, and significantly reduced expression levels of the ferritin autophagic cargo receptor NCOA4 (nuclear receptor coactivator 4) and the proteins FTH1 and p53 in the cells [ 134 ].…”
Section: Biological Aspects Of Ferroptosis Modulatorsmentioning
confidence: 99%
“…STEAP3 influences ferroptosis and RCC progression via the p53/xCT pathway [63]. Studies have demonstrated that [129]. Icariside II caused ferroptosis via modulation of the miR-324-3p/GPX4 axis in RCC cells [130].…”
Section: Pharmacological Progress Of Ferroptosis In Kidney Diseasesmentioning
confidence: 99%
“…Kerimoglu et al [128] revealed that the cyst(e)inase-rapamycin combination caused ferroptosis in both in vitro and in vivo models of hereditary leiomyomatosis and RCC. Evidence indicated that curcumin made ccRCC less resistant to sunitinib by causing ferroptosis through ADAMTS18 to treat ccRCC [129]. Icariside II caused ferroptosis via modulation of the miR-324-3p/GPX4 axis in RCC cells [130].…”
Section: Pharmacological Progress Of Ferroptosis In Kidney Diseasesmentioning
confidence: 99%